Respuesta :

NotWac

Answer:

P(A) ≠ P(D)

Step-by-step explanation:

P(A|D) = P(AD)/P(D)

P(D|A) = P(AD)/P(A)

The two denominators are not equal, so the quotients cannot be equal.

Answer:

P(A) ≠ P(D)Step-by-step explanation:P(A|D) = P(AD)/P(D)P(D|A) = P(AD)/P(A)The two denominators are not equal, so the quotients cannot be equal.

Step-by-step explanation:

P(A) ≠ P(D)Step-by-step explanation:P(A|D) = P(AD)/P(D)P(D|A) = P(AD)/P(A)The two denominators are not equal, so the quotients cannot be equal.

ACCESS MORE